Manufacturing Outsourcing A Knowledge Perspective - Rolstadås, Asbjørn; Henriksen, Bjonar; O'Sullivan, David; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
All companies which reach a critical size are faced with outsourcing decisions that can increase the value of their products and services primarily through lower costs, greater reliability and improved efficiency. Successful outsourcing decisions have an important knowledge dimension, where the outsourcing professionals need to be supported by historical and contextual knowledge regarding their own products performance but also the performance of suppliers. Outsourcing in Manufacturing: the Knowledge Dimension explains in detail how a manager can acquire, create, transfer and use knowledge that optimizes their outsourcing decisions and improves the changes of marketplace success.              Outsourcing in Manufacturing: the Knowledge Dimension gives examples of the key decisions that needs to be taken by managers regarding effective outsourcing. Decisions are divided around the structural and infrastructural aspects of outsourcing and the key knowledge that needs to be managed to support good decisions. The book contains illustrations and examples of key processes throughout and concludes with a section dedicated to case studies. These case studies represent a variety of manufacturing system types and sizes focused on supply chain integration, and which deploy various manufacturing paradigms including craft, mass, lean, adaptive, and sustainable manufacturing.   Outsourcing in Manufacturing: the Knowledge Dimension covers many theoretical and practical examples of critical outsourcing decisions, their knowledge aspects and how knowledge challenges can be dealt with in a systematic way. It provides a key resource for students, lecturers and industry managers looking to solidify their understanding and application of outsourcing decision making strategies.
Part 1.Trends in Manufacturing -- 1.Taking control of the company’s destiny through knowledge -- 2. Drivers for change in manufacturing -- 3. Manufacturing in a strategic context -- 4. Evolving paradigms in manufacturing -- 5. The knowledge dimension -- Part 2. 6.Industrial outlook -- 7. Indicators and initiatives for industrial renewal -- 8. Research roadmaps in manufacturing -- 9. How well are we doing? -- Part.3 Outsourcing –strategic opportunities -- 10. Manufacturing strategies, created through decisions -- 11. Make or buy? -- 12. The geographical footprint -- 13.Approaching the partner selection and location decision -- 14. Dealing with complexity – infrastructure decisions -- Part 4. Innovation and knowledge transfer -- 15.The innovation process -- 16. What is knowledge? -- 17. Knowledge creation -- 18. Knowledge transfer and distance -- 19. Knowledge transfer and manufacturing -- 20. Outsourcing and sustainability.
Keywords: Engineering economics; Engineering economy; Production management; Industrial organization; Engineering Economics, Organization, Logistics, Marketing; Operations Management; Industrial Organization